Advances in the Masquelet technique: Myeloid-derived suppressor cells promote angiogenesis in PMMA-induced membranes. (May 2020) - Wang, Wenkai; Zuo, Rui; Long, Haixia; Wang, Yanqiu; Zhang, Yang; Sun, Chao; Luo, Gang; Zhang, Yuan; Li, Changqing; Zhou, Yue; Li, Jie
Abstract: The periosteum plays a critical role in bone formation and defect reconstruction. The concept of tissue engineering in the periosteum has been suggested to solve the clinical problems related to bone defect repair. Insertion of polymethyl methacrylate (PMMA) bone cement can induce the autologous generation of a tissue-engineered periosteum and has been considered as a promising strategy for bone defect reconstruction. The PMMA-induced membrane is a crucial element in the reconstruction of bone defects, especially for angiogenesis, but its biological mechanism remains elusive. Here, a PMMA-induced membrane model was established using a femoral critically sized defect in mice. We identified myeloid-derived suppressor cells (MDSCs) as a regulatory component of induced membrane vascularization. The increased number of MDSCs was markedly linked to increased membrane thickness and capillary density. Importantly, the results of an in vitro coculture assay indicated that MDSCs of the induced membrane further facilitated the angiogenic capacity of human umbilical vein endothelial cells (HUVECs) by upregulating the expression of VEGFA, Ang2 and HIF-1α. Furthermore, signaling pathway blockade results suggested that STAT3 activation is involved in the upregulation of VEGFA, Ang2 and HIF-1α expression in induced membrane MDSCs. Our findings provide new insights into the mechanism of angiogenesis in the PMMA-induced membrane and confirm the key signaling molecules of MDSCs in induced membrane angiogenesis. Based on these results, this strategy may become a new therapy for the treatment of large bone defects in the future. Statement of Significance: In this study, we established an autologous tissue-engineered periosteum – PMMA-induced membrane, which was formed by the foreign body reaction to PMMA bone cement. The induced membrane establishes a blood supply for the large bone defect healing. After investigation, our study discovered the critical cell type in the formation and angiogenesis processes of the induced membrane, myeloid-derived suppressor cells (MDSCs). We revealed that MDSCs of the induced membrane promote the angiogenesis of endothelial cells through the expression of VEGFA, Ang2 and HIF-1α, which was upregulated by the activation of STAT3 signaling. Our findings clarified the beneficial effect of MDSCs in the angiogenesis of bone repair, and offered an additional target for the study of foreign body reactions to bone repair materials. Graphical abstract: Image, graphical abstract